Developing guidelines for informing safe laboratory management practices for the chemical industry in Thailand - Ketkoom, Natthakarn; Nopparat, Pattama; Vorasapavit, Chantarat; Deedoungpan, Sattiya (Bulletin of Applied Sciences, 2022)
The impact of chemicals, chemical substances and hazardous substances, is still a problem and affects the current society. It consists of the growth of industries related to chemical products. Additionally, the rate has continued to rise. Chemical Industrial activities are highly possible to use a large number of hazardous chemicals. Also, there are likely to be risks from the use of hazardous chemicals. In additional, the chemical management is not correct and appropriate enough resulted to its effects the environment. The purpose of this research is to study the current chemical management and develop guidelines for Informing the chemicals management and safety in the chemical industry. The survey method was used with a designed questionnaire and the personnel development tool in chemical management was also employed. By providing training courses that cover chemical process management in chemistry laboratory. Results found that 3 main factors affecting the informing of safe chemical management practices for the chemical industry are consisting of 1. safety management system in the organization. 2. chemical safety measures. 3. safety management in the laboratory. For in-depth interview results found that chemical management and safety in the laboratory depend on the policy and vision of the management by executives in the organization support these matters.